Exploring a regional repair network with a public funding scheme for customer repairs: The 'GRAZ repariert'-case. (15th March 2021) - Lechner, Gernot; Wagner, Marcel Josef; Diaz Tena, Anna; Fleck, Christopher; Reimann, Marc
Abstract: Repair is an essential part of the transition towards a circular economy by recovering full functionality of faulty products or components, and thus, extending the product usage phase. This is seen as a core strategy to obtain desired environmental impact like waste reduction and resource conservation. Beyond that, repair services also affect societal and economic aspects like the number of local jobs. To realize the potential, supply with as well as demand for repair services has to be ensured. In this study we report on how the city of Graz, Austria deals with challenges related to this by introducing a public funding scheme for repair services to increase demand, and funding and organizing a repair network to strengthen the suppliers. By means of a case study, we explore success factors and critical aspects related to setting up a repair network, and provide insights into the interplay of a financial incentive scheme for promoting repair. Key findings show that: (1) having the local government as the network organizer facilitates the integration of multiple sectors but might jeopardize the network's sustainability due to political reasons; (2) the interplay between public funding and the repair network is effective, but network heterogeneity induces risk; (3) cooperation within the network can improve price and service quality and thus, affect customer demand, but lacking awareness of repair in general and the repair network constrains demand. These insights and the related discussion result in the identification of future research opportunities and related questions.